Localized English for Ngapak Javanese Speakers as Language Instruction - As Sabiq, Agus Husein (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This study aimed to investigate the use of local dialect as language instruction in the English classroom and its demotivating factors for Ngapak Javanese speakers. There were four English teachers and 132 students from four schools in the Ngapak Javanese community participating in this research by semi-structured interviews and questionnaires. The findings showed that local variety influenced students’ phonological features, stressing, and intonation. The teachers were indicated having positive attitudes toward the use of local dialect of English. However, they provoked the students to use Bahasa Indonesia as their second language in switching and mixing the code in the teaching and learning process. Lack of vocabulary mastery was also one of the obstacles faced by the teachers. Teachers' perception of the most appropriate implementation of language instruction, teaching strategies, learning resources, and media may lead them to deliver the instruction properly and effectively in improving students’ proficiency. Ngapaknese English could be suggested as a pedagogical implication in the sense of Western Central Java because it is more popular, feasible and practical for students. It also has realistic values in classes, including inspiring students to practice speaking, feasible and cost-efficient.